MODEL BIMBINGAN KESEHATAN MENTAL UNTUK PARA SANTRI PONDOK PESANTREN SYAFIâ€™IYAH CISAMBENG MAJALENGKA - Yedi Supriadi (Oasis : Jurnal Ilmiah Kajian Islam, 2017)
The goalÂ  of the researchÂ  areÂ  to describeÂ  the development of the mental healthÂ  for young students at the boardingÂ  school in the islamic school of Syafi'iyyah in Cisambeng city ofÂ  Palasah-MajalengkaÂ  regency.Â  DevelopmentÂ  ofÂ  mentalÂ  healthÂ  inÂ  questionÂ  isÂ  withÂ  the planting of character and morals and a healthy mental approach to the students through some methode is calledÂ  â€œshuhbahâ€ (friendship)Â  for theÂ  purposeÂ  of mentalÂ  development canÂ  be achieved easily, accurately,Â  effectively and efficiently. The method of the researchÂ  are using descriptiveÂ Â  methodÂ Â  withÂ  collectingÂ Â  someÂ Â  information,Â Â  byÂ  techniquesÂ Â  gainedÂ Â  through observation,Â  interviews, questionnairesÂ  and documentationÂ  study. DataÂ  retrievalÂ  is derived from respondents who are seen mental health problems with a purposive sampling technique that aims to find out what the problem occurs in teenagersÂ  these students then how after he followed theÂ  guidanceÂ  of mentalÂ  healthÂ  atÂ  boardingÂ  Syafi'iyyah CisambengÂ  approachÂ  by â€œshuhbahâ€ (friendship). Islamic conseling emphasizes spiritualÂ  solutions based on love and fear of Allah and the duty of fulfil our responsibility as the servants of Allah on this earth.The results of the researchÂ  illustrateÂ  that the applicationÂ  of mental health counseling with shuhbah (friendship) perceived benefit to the students who participatedÂ  in mental health counseling becauseÂ  after being interviewed and completed questionnairesÂ  the students who have experienced problems of mental disordersÂ  (misconduct) after obtaining calculatedÂ  the mean category average high.Based on the recognitionÂ  of the students,Â  they areÂ  feel much betterÂ  afterÂ  attending mental health trainingÂ  activities in Pondok PesantrenÂ  Syafi'iyyah Cisambeng guided by Mas Nawawi (Ustd.Muhamad Nawawi Fathulloh, M.Pd.I). Thus the results of this study presented a picture of the actual conditions in the field as the information and report the study authors.Â Keywords: Model Guidance, Mental Health,Â  and Pupils